2019
DOI: 10.1088/1742-6596/1378/2/022009
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Radon Concentration Survey in Bank Basements in Three Nigerian Cities

Abstract: Basement workplaces are considered as confined environment with challenging indoor air quality having higher than normal pollutants particularly that of soil gas origin. Radon a major soil gas infiltrates and accumulates within indoor spaces and becomes harmful in the absence of natural or mechanical ventilation. Radon level in bank basements in Ilorin, Lagos and Akure have been sampled and analysed in this study. The paper presents the investigations conducted to measure the radon concentration in the occupie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Adegun, et al [48] research has similarly shown that basement workplace are cramped areas with poor indoor air quality, particularly when it comes to toxins with a soil gas origin. Radon a has similarly shown that basement workplaces are cramped areas with poor indoor air quality, especially when it comes to toxins with a soil gas origin.…”
Section: Radon In Buildingsmentioning
confidence: 99%
“…Adegun, et al [48] research has similarly shown that basement workplace are cramped areas with poor indoor air quality, particularly when it comes to toxins with a soil gas origin. Radon a has similarly shown that basement workplaces are cramped areas with poor indoor air quality, especially when it comes to toxins with a soil gas origin.…”
Section: Radon In Buildingsmentioning
confidence: 99%